2018
DOI: 10.1002/nau.23481
|View full text |Cite
|
Sign up to set email alerts
|

Age‐associated urethral dysfunction in urethane‐anesthetized rats

Abstract: The results indicated that aging induces dysfunction in movement coordination between the urinary bladder and the urethra. Thus, age-associated urethral dysfunctions may lead to inefficient voiding with increased post-void residual urine volume, which is often observed in elderly populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…Thus, it is thought to be part of the coordinated urethral activity during bladder contractions. Similar to our recent study (Kimura et al., 2018), the amplitude of HFOs during urethral relaxation was significantly lower in middle‐aged and aged rats than in young rats in this study. Our novel study on the triple recording of EUS‐EMG also showed bursting activity during bladder contractions with a clear AP and SP in young rats, an unclear AP and SP in middle‐aged rats, and no SP in aged rats.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, it is thought to be part of the coordinated urethral activity during bladder contractions. Similar to our recent study (Kimura et al., 2018), the amplitude of HFOs during urethral relaxation was significantly lower in middle‐aged and aged rats than in young rats in this study. Our novel study on the triple recording of EUS‐EMG also showed bursting activity during bladder contractions with a clear AP and SP in young rats, an unclear AP and SP in middle‐aged rats, and no SP in aged rats.…”
Section: Discussionsupporting
confidence: 92%
“…Urethral smooth muscle relaxation is crucial for efficient voiding. Similar to the findings of our recent study (Kimura et al., 2018), the change in UPP during bladder contractions was significantly decreased in middle‐aged (i.e., 12‐month) rats, as compared to that in young rats in this study. We also confirmed the decreased UPP change in aged rats (24 months) and obtained the same results.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations